Heterozygous CAPN3 missense variants causing autosomal‐dominant calpainopathy in seven unrelated families. (28th September 2020) - González‐Mera, L.; Ravenscroft, G.; Cabrera‐Serrano, M.; Ermolova, N.; Domínguez‐González, C.; Arteche‐López, A.; Soltanzadeh, P.; Evesson, F.; Navas, C.; Mavillard, F.; Clayton, J.; Rodrigo, P.; et al.
Abstract : Aims: Recessive variants in CAPN3 gene are the cause of the commonest form of autosomal recessive limb girdle muscle dystrophy. However, two distinct in‐frame deletions in CAPN3 (NM_000070.3:c.643_663del21 and c.598_621del15) and more recently, Gly445Arg and Arg572Pro substitutions have been linked to autosomal dominant (AD) forms of calpainopathy. We report 21 affected individuals from seven unrelated families presenting with an autosomal dominant form of muscular dystrophy associated with five different heterozygous missense variants in CAPN . Methods: We have used massively parallel gene sequencing (MPS) to determine the genetic basis of a dominant form of limb girdle muscular dystrophy in affected individuals from seven unrelated families. Results: The c.700G> A, [p.(Gly234Arg)], c.1327T> C [p.(Ser443Pro], c.1333G> A [p.(Gly445Arg)], c.1661A> C [p.(Tyr554Ser)] and c.1706T> C [p.(Phe569Ser)] CAPN3 variants were identified. Affected individuals presented in young adulthood with progressive proximal and axial weakness, waddling walking and scapular winging or with isolated hyperCKaemia. Muscle imaging showed fatty replacement of paraspinal muscles, variable degrees of involvement of the gluteal muscles, and the posterior compartment of the thigh and minor changes at the mid‐leg level. Muscle biopsies revealed mild myopathic changes. Western blot analysis revealed a clear reduction in calpain 3 in skeletal muscle relative to controls. Protein modelling of these variants on the predicted structure of calpain 3 revealed that all variants are located in proximity to the calmodulin‐binding site and are predicted to interfere with proteolytic activation. Conclusions: We expand the genotypic spectrum of CAPN3 ‐associated muscular dystrophy due to autosomal dominant missense variants. Abstract : González‐Mera et al. report on five different heterozygous missense variants in CAPN3 in seven unrelated families suffering from an autosomal‐dominant limb girdle muscular dystrophy.